2013
DOI: 10.4028/www.scientific.net/amm.477-478.481
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Organic Matter Content on Soil Moisture Dynamics

Abstract: Organic matter plays an important role in soil moisture variation. In order to know the effect of organic matter on soil moisture dynamics, this study compared the infiltration and evaporation of soils with different organic matter content. The results showed that increasing the organic matter content in a certain degree can suppress evaporation and infiltration of soil moisture, and hence improving water use efficiency. When the organic matter content reaches3.2%, effect of suppressing evaporation is most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The information presented herein indicates the beneficial effects of restoring SOM content in either alleviating drought or reducing its severity and duration by enhancing PAWC of the root zone (Table 5). The SOM‐induced improvement in soil health can lead to drought‐resilient soil (Sullivan, 2002), suppress evaporation (Ding et al., 2014), and reduce the need for any additional irrigation (Klein & Klein, 2015). Iizumi and Wagai (2019) reported that even a small increase in topsoil‐SOM content could enhance drought tolerance of the food production systems over 70% of the global harvested areas, especially in drylands of the world.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The information presented herein indicates the beneficial effects of restoring SOM content in either alleviating drought or reducing its severity and duration by enhancing PAWC of the root zone (Table 5). The SOM‐induced improvement in soil health can lead to drought‐resilient soil (Sullivan, 2002), suppress evaporation (Ding et al., 2014), and reduce the need for any additional irrigation (Klein & Klein, 2015). Iizumi and Wagai (2019) reported that even a small increase in topsoil‐SOM content could enhance drought tolerance of the food production systems over 70% of the global harvested areas, especially in drylands of the world.…”
Section: Methodsmentioning
confidence: 99%
“…Land use and soil management can impact SWR by altering SOM content, aggregation, porosity, and pore-size distribution, surface runoff versus infiltration, and evaporation and deep drainage ( Figure 1). Increase in SOM content can suppress evaporation and F I G U R E 1 Factors affecting the impact of soil organic matter content on soil water retention and plant available water capacity infiltration of water (Ding, Huang, Wang, Zhang, & Zhang, 2014). Complex and strongly interacting factors make it a daunting methodological challenge to establish the direct cause-effect relationship between SOM content and SWR or PAWC.…”
Section: Soil Organic Matter Content and Water Retentionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soil water movement processes are closely linked to soil organic matter content. Organic matter can reduce evaporation and improve water conservation and water supply performance [13][14][15]. Organic matter also significantly affects moisture retention [16], the characteristic curve of soil moisture [17], and thermal conductivity [18], which contribute to evaporation.…”
Section: Introductionmentioning
confidence: 99%